Hidden Talent : The Emergence of Hollywood Agents - Kemper, Tom (Book collections on Project MUSE., 2010)
This is a history of Hollywood agents as they rose in the studio system in the late 1920s and early 1930s up through the 1940s, demonstrating the central role they played in the classical Hollywood period.